Dissertações & Teses - Bundt, Roger Luiz da Cunha; Costa, Bruno César Simões; Trevisan, Michele Kapp; Kopp, Rudinei; Cardoso, Roberta Mânica; Silva, Lisiane Vasconcellos da; Hartmann, Nadja Maria; Felizardo, Cristina Kessler; Müller, Eduardo Fernando; Teixeira, Marieli Rangel; et al. (Revista FAMECOS, 2011)
.